Analysis of Delay In Execution of Construction Projects - Muralidhar, P.; Kumar Jain, Rahul; Srivasta, B.; Poorna Chandra Rao, V. (Journal of Civil Engineering, Science and Technology, 2018)
The construction industry is one of the major sectors that provide important ingredients for the development of country’s economy. A survey is conducted to identify the major causes of construction delays, its effects, and minimizing delays in construction projects using relative importance index method. The questionnaire was circulated among various construction companies located in India to find the reasons which are affecting the construction projects in India. The various factors are identified for this purpose and these critical factors are then categorized into owner, contractor, consultant, material, design, labor, equipment and external factors. About fifty six responses are received for the analysis purpose. SPSS software is applied to perform the analysis. The survey is concentrated on the frequency of occurrence of this factors and what is the severity of this factors in the five point scale.